Nanostructured Bioactive Polymers Used in Food-Packaging - L. Mateescu, Andreea; V. Dimov, Tatiana; M. Grumezescu, Alexandru; C. Gestal, Monica; C. Chifiriuc, Mariana (Current Pharmaceutical Biotechnology, 2015)
The development of effective packaging materials is crucial, because food microorganisms determine economic and public health issues. The current paper describes some of the most recent findings in regards of food preservation through novel packaging methods, using biodegradable polymers, efficient antimicrobial agents and nanocomposites with improved mechanical and oxidation stability, increased biodegradability and barrier effect comparatively with conventional polymeric matrices.
Keywords: food safety